THE EFFECTIVENESS OF THE COMBINATION OF BIRTH BALL EXERCISE AND HUSBAND’S SUPPORT ON THE PROGRESS OF CHILDBIRTH IN PHASE I AND THE LEVEL OF MATERNAL ANXIETY IN BALIKPAPAN - Nila Trisna Yulianti; Murat Arslan (Journal of World Future Medicine, Health and Nursing, 2026)
The process of labor is often accompanied by physical discomfort and emotional stress, which can influence its progression and the overall experience of childbirth. Birth ball exercises and spousal support have been identified as effective interventions to alleviate labor-related discomfort and anxiety. However, the combined effect of these interventions remains underexplored, particularly in the Indonesian context. This study aimed to assess the effectiveness of combining birth ball exercises and spousal support on labor progression and maternal anxiety during the first stage of labor in Balikpapan. A quasi-experimental design with a pre-test and post-test approach was used, involving 60 first-time mothers who were randomly assigned to either an experimental group (birth ball exercises and spousal support) or a control group (standard care). Data on cervical dilation, contraction frequency, and labor duration were collected, alongside anxiety levels measured by the State-Trait Anxiety Inventory (STAI). The results indicated that the experimental group experienced faster labor progression and significantly lower anxiety levels compared to the control group. The study concluded that combining birth ball exercises with spousal support can effectively improve labor outcomes and reduce maternal anxiety. These findings suggest the integration of these interventions into routine prenatal care to enhance maternal well-being and labor efficiency.